Menata Keterwakilan Perempuan Di Dpr Ri Berdasarkan Prinsip Keadilan, Ham, dan Demokrasi - RR Cahyowati; Rodliyah - (Fakultas Hukum Universitas Mataram, 2012)
The issues raised in this writing due to the regulating on the women representation in DPR RI (the Parliament of Republic Indonesia) based on the justice, HR, and democracy principles. By analyzing the Act of Political Party, and the Act of General Election basedon the justice, HR, and democracy principles, Research methods, this studyis anormativelegal research, with theapproachof legislation, approachesthe concept, approach tophilosophy, andthe comparative approach.May be concluded that the regulating of based on the justice, HR, and democracy principles, may be concluded that the regulating the women representation in DPR RI based on the justice, HR, and democracy principles, namely by reformulating temporary special action/affirmative actionin the Act of Political Party, and the Act of General Election, must care to minimal 40% of the women representation, by considering the more women recruited by parpol (political parties) the more opportunity of women to the members of DPR RI. The placement of the list of candidates uses zipper system so that no vacuum in ordering the list of the candidates by crossing between women and men, and delivers administrative sanction to the parpol violate the minimal quote 40% of the women representation in the potent of the candidate of legislative members by excepting the parpol to participate in the pemilu (the general election).